Economic Geology of Natural Gas Hydrate - Max, Michael D. (Coastal Systems and Continental Margins,, 2006)
This is the first book that attempts to broadly integrate the most recent knowledge in the fields of hydrate nucleation and growth in permafrost regions and marine sediments. Gas hydrate reactant supply, growth models, and implications for pore fill by natural gas hydrate are discussed for both seawater precursors in marine sediments and for permafrost hydrate. These models for forming hydrate concentrations that will constitute targets for exploration are discussed, along with exploration methods. Thermodynamic models for the controlled conversion of hydrate to natural gas, which can be recovered using conventional industry practices, suggest that a number of different types of hydrate occurrence are likely to be practical sources of hydrate natural gas. Current progress in the various aspects of commercial development of hydrate gas deposits are discussed, along with the principal extractive issues that have yet to be resolved. Audience The book will be of interest to petroleum geologists, earth scientists (marine geology and geophysics), government departments and institutions concerned with energy resources.